Attributing Controlling Factors of Acidification and Hypoxia in a Deep, Nutrient-Enriched Estuarine Embayment - Zeldis, John R.; Currie, Kim I.; Graham, Scott L.; Gall, Mark P. (Frontiers in Marine Science, 2022)
Measuring and attributing controlling factors of acidification and hypoxia are essential for management of coastal ecosystems affected by those stressors. We address this using surveys in the Firth of Thames, a deep, seasonally stratified estuarine embayment adjoing the Hauraki Gulf in northern Aotearoa / New Zealand. The Firth’s catchment has undergone historic land-use intensification transforming it from native forest cover to dominance by pastoral use, increasing its riverine total nitrogen loading by ~82% over natural levels and switching it’s predominate loading source from offshore to the catchment. We hypothesised that seasonal variation in net ecosystem metabolism (NEM: dissolved inorganic carbon (DIC) uptake/release) will be a primary factor determining carbonate and oxic responses in the Firth, and that organic matter involved in the metabolism will originate primarily by fixation within the Firth system, and be driven by catchment dissolved inorganic nitrogen (DIN) loading. Seasonal ship-based and biophysical mooring surveys across the Hauraki Gulf and Firth showed depressed pH and O2 reaching pH levels ~7.8 and O2 levels ~4.8 mg L-1 in autumn in the inner Firth, matched by shoreward increasing nutrient loading, phytoplankton, organic matter, gross primary production (GPP) and apparent O2 utilization. A carbonate system deconvolution of the ship survey data, combined with other ship survey and mooring results, showed how CO2 partial pressure responded to seasonal shifts in temperature, NEM, phytoplankton sinking and mineralisation and water column stratification, that underlay the late-season expression of acidification and hypoxia. This aligned with seasonal shifts in net DIC fluxes determined in a coincident nutrient mass-balance analysis, showing near-neutral fluxes from spring to summer, but respiratory NEM from summer to autumn. Particulate C:N and ratios of organic C fixed by Firth GPP to that from river inputs (~29- to 100-fold in summer and autumn) showed that the dominant source of organic matter fuelling heterotrophy in autumn was autochthonous GPP, driven by riverine DIN loading. The results signified the sensitivity of deep, long-residence time, seasonally stratifying estuaries to acidification and hypoxia, and are important for coastal resource management, including aquaculture developments and catchment runoff limit-setting for maintenance of ecosystem health.